Mowa niezależna w przekazie medialnym a podstawowe funkcje informacji dziennikarskiej (część 2) - Grzelka, Monika; Kula, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
This article reports part of a research project currently carried out by the authors devoted to the analysis of quoted speech used by Polish journalists in their discourse after 1989. The first part of the article was published in the previous volume of Poznańskie Studia Polonistyczne. The present part focuses on the characteristics of the participants (parties) in journalistic information. Prevailing and determining factors related to the number and the type of participants in journalistic information are presented, and fundamental functions of speech verbs (verba dicenti) are indicated. Citation is the most explicit form of inclusion of other-discourse in one’s discourse. The second part of the study provides more detailed analysis that includes the following categories: the category of witnesses, experts (practitioners) and that of experts (theoreticians). The third part of the article is due to be published soon.